Background information in the discussion sections of forestry journals: a case study - Renu Joseph; Lim, Jason Miin-Hwa (Penerbit Universiti Kebangsaan Malaysia, 2018)
The Discussion section constitutes a powerful closing argument used by a researcher to highlight key findings in relation to the existing knowledge with the aim of facilitating readers’ comprehension of the entire study. As previous research has yet to identify the frequencies of the different types of background information and the language resources used to present them, this study sought to identify the types of background information employed by expert writers, ascertain the frequencies and positions of the information concerned, and explore how expert writers use lexico-grammatical resources to present such information in the Discussion sections of Forestry research reports. Using a genre-based analytical framework, 60 Discussion sections in Forestry journals were studied. The findings revealed that provision of essential background information is a principal communicative move appearing in 95% of Forestry Discussion sections. This section comprises (i) contextual and theoretical information aimed at facilitating readers’ comprehension of the findings to be presented, and (ii) a reiteration of objectives, methods and/or hypotheses of the research. Based on the findings, it is suggested that background information be highlighted to learners as a segment that serves a promotional function which emphasises the significance of their research topic in relation to the plenitude of past studies. Using the language resources identified in this study, it is recommended that lecturers teaching English for Research Purposes (ERP) focus on the use of (i) adjectives denoting prominence, (ii) investigative and procedural verbs, (iii) means and purposive adjuncts, and (iv) infinitive clauses describing expected behaviours in order to help learners clearly furnish relevant background information.